Effect of Erosive‐Abrasive Challenge and Surface Finishing Protocols on Optical Properties and Microhardness of CAD‐CAM Ceramics - Zaniboni, Joissi Ferrari; Silva, Amanda Soares [UNESP]; Silva, Aryvelto Miranda; Besegato, João Felipe; de Campos, Edson Alves [UNESP] (Wiley, 2025)
PURPOSE: To evaluate the effect of erosive-abrasive challenge on the optical properties, microhardness, and surface morphology of CAD-CAM ceramics with different surface finishing protocols. METHODS: CAD-CAM ceramics used were: IPS e.max CAD (DIS), IPS Empress CAD (LEU), Cerec Blocs (FEL), and Celtra Duo (CEL). Specimens were divided into five groups (n = 10): Polishing (P), Conventional Glaze (CG-control), Conventional Glaze with 2 firings (CG2), Extended Glaze firing (EG), and Extended Glaze with 2 firings (EG2). An erosive-abrasive challenge was performed with citric acid and simulated toothbrushing. Color change (ΔE00), translucency, contrast ratio, gloss, Vickers microhardness, and surface morphology were evaluated. The evaluations were performed before and after the erosive-abrasive challenge. ΔE00 was analyzed with one-way ANOVA with Welch correction and Games-Howell, while the other data were evaluated with two-way repeated measures ANOVA and Bonferroni post-test (α = 0.05%). RESULTS: After the challenge, CG groups showed clinically unacceptable color changes. Translucency decreased in LEU-P, FEL-P, FEL-EG, and CEL-EG groups, but increased in DIS-CG2, DIS-EG2, and CEL-EG groups. The contrast ratio was close to 1. No gloss reduction was observed in CG groups. Microhardness decreased in DIS-EG, DIS-EG2, LEU, FEL, and CEL groups, but remained unchanged in LEU-CG, FEL-CG2, and CEL-EG2 groups. CONCLUSION: Erosive-abrasive challenge affected the properties of CAD-CAM ceramics with different behaviors depending on the surface finishing protocol used. CLINICAL SIGNIFICANCE: The optical properties and microhardness of CAD-CAM ceramics are negatively affected by erosive-abrasive conditions. Manual polishing showed similar performance in maintaining these properties and may represent a viable and effective alternative to glaze application.